Pelatihan Pengembangan Media Pembelajaran 3D Pada Guru PAUD Desa Gabusbanaran - Muhammad Farid Nasrulloh; Khusnul Khotimah; Zumroturrohma Dwi Apriliana; Mokhamad Choirul Muadhom; Titik Puspasetya Puspasetya (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2022)
Early Childhood Education (PAUD) as preschool education is actually a new educational institution in Indonesia when compared to the existence of Kindergartens (TK) under the authority of the Ministry of Education and Culture, as well as Raudhatul Atfal (RA) under the responsibility of the Ministry of Religion. These two preschool educational institutions have been active in educating the nation's children through playing while learning. The purpose of community service regarding the implementation of 3D learning media for PAUD about animals is to achieve PAUD children's understanding of tame animals or wild animals. The approach or method used is Service Learning (SL). The Service Learning service method is one approach in teaching that combines academic goals in an effort to raise awareness in solving problems directly. Implementation of community service on the application of learning media about animals for PAUD students get satisfactory results. This is because when the process of applying the learning media, almost 80% of students take part in learning with enthusiasm. They were very enthusiastic about listening to the explanation from the community service maker because of the learning media that was packaged like a mini zoo so that students felt interested.